PENGARUH REALISASI PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP REALISASI PENDAPATAN ASLI DAERAH (PAD) KOTA CILEGON TAHUN 2014-2018 - Sev Rahmiyanti; Didit Prasetyo (FKIP, Universitas Banten Jaya, 2020)
This research was conducted to determine the effect of local taxes and levies on local revenue. This study uses data on the realization of the Regional Expenditure Budget and is devoted to the data on the realization of the revenue of the original region of Cilegon which was taken over a period of five years, starting from 2014 until 2018. The data was obtained from the Badan Pengelolaan Keuangan dan Aset Kota Cilegon with the type of data used is time series data.The results of this study indicate the effect of local tax revenue and regional retribution in the city of Cilegon have a positive effect simultaneously on the increase of local revenue with a magnitude of influence of 94.8%, while partially local tax and regional levies have different influences in influencing local revenue. It can be concluded that regional taxes have a significant effect on local own-source revenues while regional user fees do not have a significant effect on regional own-source revenues.